Academic self-efficacy scale of college students in Lima - Robles Mori, Herbert (2020)
The present research had the purpose of proposing and validating a scale of academic selfefficacy in a university student group. The sample consisted of 340 students, the type of study was psychometric, in the present study the scale of academic self-efficacy (ESAA) was elaborated in a multidimensional way. The results indicated that there is a content validity (Aiken V = .94), a reliability (Cronbach’s alpha of .877) and construct validity with two factors: expectation of the situation and personal expectations, within the latter finds expectations of results andexpectations of perceived self-efficacy. It was concluded that the ESAA scale, has the psychometric characteristics to be considered valid and reliable.